Impactos da afetividade em aulas de música: o que dizem as narrativas infantis - Andrea Matias Queiroz (2024)
This research was developed as part of the Graduate Program in Music at the Federal University of Minas Gerais (UFMG) and aimed to understand how affectivity can influence music classes for children in the early years of elementary school, based on their own perceptions, in the context of a regular school. I took this objective to mean: investigating what musical experiences children are having in their music classes; understanding what meanings the children attribute to music classes at school; identifying how they perceive, relate to and interact affectively with music in this environment. As a literature review, I bring up studies that deal with themes related to this research, such as the influences of affectivity in music classes and Narrative research carried out from the children's perspective. The theoretical framework used to illuminate the empirical field researched was developed from concepts that deal with Cognitive Psychology in the field of learning, seeking to understand cognition and affectivity through Henry Wallon's psychogenetic theory. The empirical field of this research was two schools located in the city of Brasília – DF, one public and the other private, and the research subjects were students in 5th grade classes. In terms of methodology, this is qualitative research with a narrative approach, where the subjectivity of the individuals becomes a fundamental point of the study. The research technique combines arts-based-research with conversation circles, since both, in some way, use playfulness in their process to bring out the interviewees' experiences. Looking at the musical experiences of these children, based on their own conceptions, led to an understanding of the need to work on positive affective relationships in music classes, as it is through these relationships that they remain engaged in the process of learning music. I also highlight the importance of listening to and considering children's perceptions of music in their lives, given that they are the protagonists of their own lives and have a unique and valid understanding of their experiences.